Analisis Kinerja Keuangan Pt. Telkom Tbk Sebelum Dan Sesudah Launching Produk Speedy (Studi Kasus Pada Pt. Telkom Tbk Purwodadi) - Santini, Mei (2016)
The purpose of this study was to determine the profitability ratio, liquidity ratio, solvency ratio, activity ratio, operating income, operating expenses and net income at PT. Telkom Purwodadi. This study used qualitative research methods in the form of financial statements. Telkom Purwodadi. Data were obtained from the results of documentation, interviews, and observations. Triangulasi.Serta validity of the data using data analysis used is descriptive analysis comparative analysis techniques comparative financial statements, ratio analysis and conclusion. Results of the study found that once held the analysis of financial performance that consisted of profitability ratios, liquidity ratios, solvency ratios, activity ratios between before and after the product launch speedy average not increased significantly, operating income before and after the product launch speedy increase Rp 941,685.00, operating expenses before and after the product launch speedy increased USD 1,249,188.00 and a net profit before and after lauching speedy product increased by USD 127,191.00. Conclusions based on research results is no difference between the average profitability ratios, liquidity ratios, solvency ratios, activity ratios, operating income, operating expenses and net income between before and after the product launch speedy. So by knowing the value of the analysis of financial performance, operating income, operating expenses and net income can be a reference and sales target PT. Telkom Purwodadi in the future and to evaluate the implementation of the program the company so that all the differences that do not benefit the company can more quickly be overcome. Mei Santini / A210110071. ANALYSIS OF FINANCIAL PERFORMANCE PT. TELKOM Tbk BEFORE AND AFTER LAUNCHING PRODUCTS SPEEDY. Publications Articles Thesis. Study Program Accounting Education, Guidance and Counseling, University of Muhammadiyah Surakarta. December 2015. The purpose of this study was to determine the profitability ratio, liquidity ratio, solvency ratio, activity ratio, operating income, operating expenses and net income at PT. Telkom Purwodadi. This study used qualitative research methods in the form of financial statements. Telkom Purwodadi. Data were obtained from the results of documentation, interviews, and observations. Triangulasi.Serta validity of the data using data analysis used is descriptive analysis comparative analysis techniques comparative financial statements, ratio analysis and conclusion. Results of the study found that once held the analysis of financial performance that consisted of profitability ratios, liquidity ratios, solvency ratios, activity ratios between before and after the product launch speedy average not increased significantly, operating income before and after the product launch speedy increase Rp 941,685.00, operating expenses before and after the product launch speedy increased USD 1,249,188.00 and a net profit before and after lauching speedy product increased by USD 127,191.00. Conclusions based on research results is no difference between the average profitability ratios, liquidity ratios, solvency ratios, activity ratios, operating income, operating expenses and net income between before and after the product launch speedy. So by knowing the value of the analysis of financial performance, operating income, operating expenses and net income can be a reference and sales target PT. Telkom Purwodadi in the future and to evaluate the implementation of the program the company so that all the differences that do not benefit the company can more quickly be overcome. Keywords: financial performance, operating income, operating expenses, net income